Meningkatkan Kemampuan Sastra Anak dalam Pembelajaran Bahasa dan Sastra Indonesia dengan Menggunakan Kartu Kata, Video Cerita Pendek, dan Teks Deskripsi Untuk Siswa Kelas Rendah - Yohana Nono BS; Chatarina Novianti; Maria Ludtinia Bupu Meo; Sebastiana Nenu (Lembaga Pengembangan Kinerja Dosen, 2025)
The low interest and engagement of lower-grade primary school students in literature serve as an important introduction to this study. The aim of this Community Service Program (PKM) was to enhance children’s literary abilities through the use of three innovative media: word cards, short story videos, and descriptive texts. The study employed an experimental method with a pretest–posttest control group design and a Classroom Action Research (CAR) approach based on Kemmis & McTaggart (1988), carried out among grades I–III students at SD Katolik Roworeke 2, Ende (approximately 25–30 students per class). Results showed a statistically significant improvement in the experimental group compared to the control group, especially in literary element comprehension and literary appreciation. Word cards enriched vocabulary, story videos increased visual appeal and understanding, while descriptive texts trained literacy and imagination skills. The interactive and contextual learning process proved effective in fostering reading interest, teacher creativity, and students’ literacy enthusiasm. In conclusion, this method is recommended for adoption by Indonesian Language and Literature teachers in lower grades. Future research should expand sample size, include diverse literary works, and explore supporting factors influencing method effectiveness.